Directed tasks as an alternative academic support vehicle for EFL second graders at Colegio Americano de Guayaquil. - Quintero Burgos, Ana MAría (2017)
This work was based on educational theories that state why it is important to address the tasks in children of the second grade of primary education, inside or outside the classroom. In the educational system it is necessary to help the child overcome this stage, due to the difficulties they present in the teaching-learning process. These difficulties were studied at Colegio Americano de Guayaquil where results showed that second graders present difficulties doing their reading activities. To tackle this issue, we introduced a directed task plan (DTP) educational strategy as a guide for English teachers of second grade of basic education to help them develop basic skills on reading and reading comprehension. The purpose of this plan is to strengthen the linguistic skills of the children and initiate the process of acquisition and construction of reading comprehension skills which will be reflected on specific aspects such as relating the previous knowledge with the new one. The beneficiaries will be teachers, parents and students of the institution. In this document a stratified sample of the population as the proportionate allocation and surveys were drawn in the Likert scale of 4 points. With the design of directed learning tasks intellectual activities could be developed such as academic assistance to children in the second grade and students that have difficulties in reading can improve their academic performance.